Hisham Sharabi: The Anatomy of Neopatriarchy and Criticism of Arab Culture - Romi Astanti (BAYAN: Jurnal Studi Islam dan Humaniora, 2026)
Contemporary Arab thought has been significantly shaped by attempts to explain the failure of modernization in the Arab-Islamic world. One of the prominent scholars contributing to this discourse is Hisham Sharabi through his concept of neopatriarchy. This article aims to analyze the concept of neopatriarchy as an instrument of social and cultural criticism developed by Sharabi to examine the problems of modern Arab society. This study employs a library research method with a philosophical-critical approach. The primary sources consist of Sharabi’s major works, particularly Neopatriarchy: A Theory of Distorted Change in Arab Society, along with various supporting literature discussing contemporary Arab socio-political thought. Data were analyzed using content analysis and critical interpretation of Sharabi’s ideas. The findings reveal that neopatriarchy represents a distorted form of modernity, a condition in which societies adopt modern institutions while simultaneously preserving traditional patriarchal patterns of relationships based on domination, obedience, and subordination. These structures are reproduced within the family, education, religion, and the state, thereby hindering the development of rationality, democracy, and individual emancipation. Sharabi’s cultural critique emphasizes the importance of deconstructing authority, reforming education, practicing cultural self-criticism (naqd al-dhat), and fostering critical consciousness as prerequisites for social transformation. Sharabi’s thought remains highly relevant for understanding various issues facing contemporary Muslim societies, particularly those related to education, power relations, and the formation of a democratic culture.